Impact of Large Poultry Operations on Groundwater : Stable 15N Isotopes of Nitrate Assessment - Showers, William J.; Williams, C.M.; Jennings, Gregory D. (International Journal of Poultry Science, 2006)
The rapid growth of livestock and poultry operations over the past 25 years has led to concern regarding environmental impacts of land applied animal wastes in many parts of the world. This study investigated the impact of dense poultry populations on ground and surface water quality in central North Carolina using the stable 15N isotopes of nitrate. On a field scale, the 15N of groundwater nitrate was not related to the type of poultry waste applied to the fields, but was controlled by the types of soils found in the litter application fields. Hydric soils had enriched groundwater nitrate 15N compositions and reduced nitrate concentrations, most likely associated with denitrification. Partially hydric and non-hydric soils did not show elevated groundwater 15N nitrate compositions. The 15N composition of groundwater nitrate in litter application fields with non-hydric soils indicates that the source of groundwater nitrate is a combination of poultry litter and fertilizer. On a watershed scale, the 15N composition of surface water nitrate was not related to the distribution of poultry operations, but was related to the distribution of hydric soils within the basin. Nitrate concentrations in stream waters remained low through out the basin studied, and the 15N composition of stream nitrate decreased downstream suggesting minimal impact on surface water quality from the surrounding poultry operations. The practice of placing poultry houses on poor quality swampy land also places them in areas dominated by hydric soils. Denitrification proceeds quickly in areas with hydric soils, which minimizes offsite nitrate transport and mitigates surface water quality impacts. This data suggests that surface water quality impacts from animal agriculture can be predicted from the spatial analysis of hydric soils within a watershed.